Real Options as an Instrument of Sustainable Growth in Banking and Portfolio Management - Jouk, Yakov (Studia Oeconomica Posnaniensia, 2017)
The main goal of the paper is to present various applications of real options in financial institution, especially banks and portfolio management com-panies, which may use it as an instrument of sustainable growth. Today, real op-tions are a hot instrument applied in different areas and industries. Despite its popularity the application of real option in banking and asset management is not so common. Sections one to six of the paper present different definitions and types of financial and real options as well as their comparison. In addition, the use of real options in different industries, with an emphasis on the banking sector is shown. Sections seven and eight discuss the sustainable growth, its definition and importance, especially in banking and portfolio management industries. Applica-tion of the real option as a tool for sustainable growth in the banking sector is also proposed. Section nine concludes the paper.